Training on the Preparing of Learning Tools as an Adjustment to the Merdeka Curriculum for Junior High School Mathematics MGMP Teachers in Lhokseumawe City - Fajriana; Fitri Ayu Ningtiyas; Nurul Afni Sinaga; Rifaatul Mahmuzah; Syahrina Intan; Puji Sabrini (CV. AFDIFAL MAJU BERKAH, 2023)
Indonesian education has implemented various curricula that have undergone improvements with each change. Currently, there is an independent curriculum designed to provide opportunities for teachers to develop teaching materials by taking into account the character, interests and talents of students. The independent curriculum has begun to be implemented in Lhokseumawe city junior high schools, but in reality this implementation is not accompanied by socialization and training related to the preparing of learning tools. This results in the teaching and learning process that occurs not in accordance with the system intended by the independent curriculum. Teachers need assistance in order to prepare learning tools so that the objectives of the independent curriculum can be achieved. One of the alternatives that can be done to overcome this problem is to conduct socialization and training in preparation of learning tools adapted to the independent curriculum for MGMP junior high School teachers in Lhokseumawe City. The purpose of this service is so that teachers, especially junior high school mathematics teachers in Lhokseumawe city who are members of MGMP, can prepare learning tools in accordance with the independent curriculum. The method used in this service is Participatory Rural Appraisal (PRA), where in this activity participants actively participate in the entire process carried out from the initial stage to the final stage. Overall, the stages of activities carried out in this service in the form of training in the preparation of independent curriculum learning tools consist of four stages, namely the planning stage, preparation stage, implementation stage, and evaluation stage. The results of this service are in the form of learning tool documents that are in accordance with the objectives contained in the independent curriculum and the satisfaction survey of training participants. Based on the results obtained from 57 respondentsit is known that the level of participant satisfaction with quality of the material presented was 90.35%.As for the aspect of the speaker, the level of satisfaction of the training participants obtained was 86.67%